An Academic Text: The Balance Between Academic Integrity and Artificial Intelligence - Ruskulis, Liliіa; Maiboroda, Rymma; Popova, Olena; Rodionova, Inna; Olecsuk, Olesia; Ababilova, Nataliia (Journal of Teaching and Learning, 2026)
This paper focuses on the connection between academic writing, academic integrity, and the fact that the application of artificial intelligence (AI) technologies in higher education is rapidly expanding, paying attention to the fundamental issue of the increasing reliance of students on AI-based technologies and the associated threat to the ethical conduct of scholarly activities. It is supported by the need to balance the pedagogical opportunities of AI with the preservation of critical thinking, originality, and responsible authorship in academic writing. In a qualitative study with a mixed design consisting of theoretical analysis, survey of students (n=248) and unstructured interviews of faculty (n=28), the authors establish the common patterns of AI use, perceptions of the students about integrity violation and the concerns of the teaching professionals about the disappearance of analytical and critical skills. The results indicate that, although AI makes academic work more accessible, personalized, and efficient, overreliance on generative systems leads to reduced cognitive effort, accidental plagiarism, and gray morality. The paper suggests a systematic, ethically aware approach to the integration of AI into higher education, with a focus on cultivating academic literacy, clearly defined institutional policies, and the pedagogic integration of AI use while preserving academic integrity standards.